Fire, destruction and creation: the art of Anselm Kiefer and the philosophy of Andrea Emo (Palíndromo, 2024)
Based on an environmental issue about the problem of forest fires in Brazil, this paper deals with the correlation between destruction and regeneration in nature and art. Taking into account tragedies caused by fire that have ruined historical and artistic heritage over time, I will analyze the affinities between an artist and a philosopher. On one side is Anselm Kiefer, with emphasis on the paintings he produced for an exhibition at the Palazzo Ducale in Venice, a place affected by a major fire in 1577; on the other, the thought of Andrea Emo, a recently rediscovered author. As will be demonstrated, the notion that images are born from iconoclastic gestures arises here as a central part of a program in which destruction and creation merge and manifest themselves everywhere.
Keywords: Anselm Kiefer; Andrea Emo; Iconoclasm; art and nature